First record of Platygaster luteipes Buhl (Hymenoptera: Platygastridae) from leaf galls on black pepper along with first report of the species from India. Issue 2 (3rd March 2016) - Anjana, M.; Rajmohana, K.; Buhl, P.N.; Shameem, K.M.
Abstract : Platygaster luteipes Buhl (Hymenoptera: Platygastridae) is reported for the first time from India. Several specimens of both sexes of the species were reared from the globular galls on mature leaves of black pepper . The hitherto undescribed male of the species is characterized and illustrated.